Q: The square root of a sum equals the sum of the square roots?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

The Pythagorean theorem states that the square of the hypotenuse of a right triangle is equal to the sum of the squares of the other two sides. 1. squares, not square roots 2. right triangle, not isosceles 3. sides opposite the hypotenuse, not any two 4. What are the mistakes, not what is

The square root of any positive integer can only be a WHOLE NUMBER or IRRATIONAL, so the square root of 7 is irrational.On the other hand, the sum of a rational and an irrational number is always irrational.

example for sum of rational numbers is 1/3 + 1/5 Example for sum of irrationals is Pi + e where e is is base of natural log Another is square root of 2 + square root of 3.

Imaginary and complex numbers are an extension of the Real Number system. They are not called unreal. An imaginary number is a non-existent number, like the square root of a negative number. For example, the square root of -4 is 2i (i stands for imaginary). There are also complex numbers, which are defined as the sum of a real number and an imaginary number (e.g. 4 + 3i). An imaginary number does not exist, but can nevertheless be useful in certain applications. An imaginary number is any number that is the product of a real number and the square root of negative one (-1). The square root of -1 is the "unit" of the set of imaginary numbers, and is referred to as "i". As you know, negative numbers cannot have square roots, and so the square root of any negative number is "imaginary". There are also "complex numbers", which are the sum of a real number and an imaginary number. For example 3 + 2i.

-2 and -3Check:(-2) + (-3) = -5(-2)(-3) = 6Thus -2 and -3 are not the required numbers. let's find them: x + y = -6xy = -5 y = -x -6x(-x - 6) = -5-x^2 - 6x = -5x^2 + 6x = 5x^2 + 6x + 9 = 5 + 9(x + 3)^2 = 14x + 3 = (+ & -)square root of 14x = -3 (+ & -)square root of 14x = -3 + square root of 14 or x = - 3 - square root of 14y = -x - 6y = 3 - square root of 14 - 6 or y = 3 + square root of 14 - 6y = -3 - square root of 14 or y = -3 + square root of 14Check:(-3 + square root of 14) + (-3 - square root of 14) = -6(-3 + square root of 14)(-3 - square root of 14) = -5 ?(-3)^2 - (square root of 14)^2 = -5 ?9 - 14 = -5Check also tow other numbers.

Related questions

It's not. Take 49 and 16 for example. The square root of the sum is the square root of 65. The sum of the square roots is 11.

The square root of 100 = 10 The square root of 225 = 15 The sum = 10 + 15 = 25

Assuming the roots are positive, then ~ 15.59.

No. The right hand side is always greater - unless both components are zero.

sqrt(15) + sqrt(25) = 5 + sqrt(15) = 8.873 (using principal roots only).

81

The sum of a [single] square equals the square.

No. The Square root of x is not the value of x. So it can not be simplified beyond: Root X + root 3x Yes. The square root of 3x equals the square root of 3 times the square root of x, so when you add another square root of x, you can factor out the square root of x, thereby simplifying the expression to the square root of x times the sum of one plus the square root of three.

You can. Just add the numbers together, and find their square root. One plus three is four; the square root of the sum is two.

If you have a data set, simply take the square root of the sum of the squares of the data points. Let's say you have three numbers a, b, and c. RSS = SQRT(a2 + b2 + c2).

Square root of 2 = 1.414213562... Square root of 7 = 2.645751311... The sum is 4.059964873...

81 -- 8+1 = 9 -- square root of 81 = 9